Vismodegib in PAMAM-dendrimers for potential theragnosis in skin cancer - Ybarra, David Emanuel; Calienni, María Natalia; Ramírez, Luis; Barraza, Felipe; Aguayo Frías, Eliana Taís; Lillo, Cristian R. (Elsevier Science, 2022)
Vismodegib (VDG) is an antineoplastic, a first-in-class Hedgehog signaling pathway inhibitor, indicated to treat locally advanced or metastatic basal cell carcinoma. Treatment with this drug was approved in 2012 by the US-FDA for oral administration (dose of 150 mg per day) in patients with a refusal of radiotherapy or surgery. However, it presents side effects that influence patient adherence to treatment. Polyamidoamine (PAMAM) dendrimers (D) are promising drug-delivery systems with high water solubility. Additionally, they can penetrate the skin barrier. In this work, we used amine-terminated (DG4.0) and carboxy-terminated (DG4.5) dendrimers of generation 4.0 and 4.5, respectively. We demonstrated that the complexation of VDG with dendrimers (D:VDG complexes) increased its concentration in the aqueous medium. We carried out characterization studies of the complexes to understand how dendrimers interact with VDG, and we found the optimal molar ratios of complexation.
Keywords: Ciencias médicas y de la salud::Biotecnología médica